Minor red blood cell antigen phenotyping of athletes sampled in international competitions - Cristina Mirotti, Luciana; Renovato Martins, Mariana; Du RocherSilva, B？rbara; DudenhoefferCarneiro, Ana Carolina; Soares, Felipe; Khandoker Asiqur Rahaman; Hasan, Mahbub; Muresan, Anca Raluca; Kwon, OhSeung; Son, Junghyun John; Pereira, Henrique Marcelo Gualberto (John Wiley & Sons Ltd., 2023)
Blood transfusion is performed by cheating athletes to rapidly increase oxygen delivery to exercise muscles and enhance their performance. This method is banned by the World Anti-doping Agency (WADA). Heterologous or allogenic blood transfusion happens when blood from a different person is transfused. The method used to detect this type of doping is based on flow cytometry, by identifying variations in blood group minor antigens present on the red blood cells' surface. Transfusion practices have regained interest since the introduction of human recombinant erythropoietin detection method. It has been reported that the number of occurrences of two athletes sharing an identical phenotype in the same sport was five times higher than the theoretical populational probability. The present work describes the prevalence of 10 erythrocytes surface antigens in a population of 261 athletes from all five continents. The matching phenotype per sport is also described.